New Paradigms for Virus Detection, Surveillance and Control of Zika Virus Vectors in the Settings of Southeast Asia - Vythilingam, Indra; Sam, Jamal I-C.; Chan, Yoke F.; Khaw, Loke T.; Sulaiman, Wan Y. Wan (Frontiers in Microbiology, 2016)
Zika virus (ZIKV) has now become a global public health concern. The vectors for ZIKV are Aedes aegypti and Aedes albopictus. Both these mosquitoes are predominant in Southeast Asia and are also responsible for the spread of other arboviral diseases like dengue virus (DENV) and chikungunya virus (CHIKV). The incidence of dengue has been increasing over the years and this is of concern to public health workers. Simple laboratory tools for the detection of ZIKV is also lacking. In the absence of drugs and vaccine for these arboviral diseases, vector control is the main option for surveillance and control. Aedes larval surveys have been the hallmark of dengue control along with larviciding and fogging when cases are reported. However, we need new paradigms and options for control of these vectors. The current situation in Southeast Asia clearly proves that effective strategies for vector control need to be proactive and not reactive. This will be the way forward to control epidemics of these diseases inclusive of ZIKV until a vaccine becomes available.